EFFECT OF CAWPEA POWDER (Vigna Unguiculata) ON THE SMOOTH PRODUCTION OF BREAST MILK IN BREASTFEEDING MOTHERS IN KEDIRI CITY - Sari, Dewi Kartika; , Sutrisni (Universitas Nahdlatul Ulama Surabaya, 2022)
Breastfeeding is giving breast milk to babies. Breast milk is needed by babies for their growth, besides that breast milk also contains complete nutrients needed by babies according to their age stages. The purpose of this study is to analyze the effect of Cowpea powder (Vigna unguiculata) on the smooth production of breast milk in breastfeeding mothers in Kediri City in 2022. This research design is a quasi-experimental study, with Two Group Pretest and Post Test design. In this study, the study population was all postpartum mothers who breastfeed on day 4 in July - August 2022. This study used accidental sampling technique. The statistic test to test the effect was using the Wilcoxon test and the test for the difference test was the Mann whitney test. The results of the study in the intervention group obtained p value of 0.003 and α of 0.05 (P_value <α: 0.05) were obtained, which means that there was an effect of giving Cowpea powder (Vigna unguiculata) on the smooth production of breast milk and in the control group obtained p value of 0.046 and a α of 0.05 (P_value <α: 0.05) were obtained, which means that there was an effect of giving cowpea powder (Vigna unguiculata) on the smooth production of breast milk. The results of the different tests found that P Value: 0.024 and α: 0.05 (P_value <α: 0.05) which means that there is a difference in the smoothness of breast milk production after receiving intervention in giving cowpea powder (Vigna unguiculata). With the influence of cowpea powder (Vigna unguiculata) on the smooth production of breast milk, it is hoped that cowpea can be used as an additional food that can support breastfeeding mothers in producing breast milk.